Noise Trading : An Analysis of Retail Trading in the Indian Equity Market - George, Saji; Srinivasa Suresh, P. (Indian Journal of Research in Capital Markets, 2015)
The investment decision making in stock markets across the globe has become a cumbersome task due to the frequent fluctuations in the stock prices and trade volume that do not commensurate with the new information flows. These occurrences can be broadly attributed to ’noise trading’ emanating from the naïve trading behaviour of investors. This study, on the assumption that noise trading increases trade volume and return variance, examined the trading behaviour of retail investors to find out if their trading creates noise in the price discovered. The Indian stock market is flooded with different categories of investors with varying resources, motives, information share, and behavioural instincts. By analyzing daily buy-sell activity together with changes in market liquidity and return variances, this study identified convincing evidence of noise in retail trading in the Indian equity market. Furthermore, these results demand analysis of the same issues in more dynamic frames of analysis covering other investor categories and direct the attention to investigate on the functioning of intermediaries in creating noise based trading in the Indian market.